Differences in motivations and weight loss behaviors in young adults and older adults in the national weight control registry12. (16th April 2013) - LaRose, Jessica Gokee; Leahey, Tricia M.; Hill, James O.; Wing, Rena R.
Abstract Objective: The goal of this study was to compare young adults (YA) and older adults (OA) in the National Weight Control Registry on motivations for weight loss and weight‐loss behaviors. Design and Methods: Participants (n = 2, 964, 82% female, 94% White, BMI = 24.8 ± 4.4) were divided into two age groups (18‐35 vs. 36‐50) and compared on motivations, strategies for weight loss, diet, physical activity (PA), and the three‐factor eating questionnaire. Results: YA were 28.6% of the sample (n = 848). YA and OA achieved similar weight losses (P = 0.38), but duration of maintenance was less in YA (43 vs. 58 months, P < 0.001). YA were more likely to cite appearance and social motivations for weight loss, were less motivated by health, and were less likely to report a medical trigger for weight loss (P's < 0.001). YA were more likely to use exercise classes and to lose weight on their own, and less likely to use a commercial program (P's < 0.001). YA reported engaging in more high‐intensity PA (P = 0.001). There were no group differences in total calories consumed (P = 0.47), or percent calories from fat (P = 0.97), alcohol (P = 0.52), or sugar‐sweetened beverages (P = 0.26). Conclusions: YA successful weight losers (SWL) are motivated more by appearance and social influences than OA, and physical activity appears to play an important role in their weight‐loss efforts. The differences reported by YA and OA SWL should be considered when developing weight‐loss programs for YA.